نزع ملكية الاستثمارات الأجنبية : دراسة مقارنة - Kareem, Shams; Fleh, Haider (Journal of Legal Sciences, 2022)
The right to property is one of the most prominent and most important of the fundamental rights that the individual enjoys, whether national or foreign, both of them have their own private property that may not be affected except for the requirements of the country's economic development or what is known as the public benefit, and the Iraqi legislator did not specify what is meant by the removal of foreign investment. Of the bilateral international agreements (BITS), as it determined its terms and methods, the properties of foreign investors may be expropriated in a direct and indirect way.